2012
DOI: 10.1016/j.matcom.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and simulation of photosynthetic microorganism growth: random walk vs. finite difference method

Abstract: The paper deals with photosynthetic microorganism growth modelling and simulation in a distributed parameter system. Main result concerns the development and comparison of two modelling frameworks for photo-bioreactor modelling. The first "classical" approach is based on PDE (reaction-turbulent diffusion system) and finite difference method. The alternative approach is based on random walk model of transport by turbulent diffusion. The complications residing in modelling of multi-scale transport and reaction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…All the values needed to perform further calculations are summarized in Table 1 (u 1 is chosen accordingly to fulfill the condition u av = 1): Similarly as in our work [16], Lagrangian time-dependent simulation (data not shown) revealed that the state vector converges to a steady state in a few minutes (this is the time-scale of the photoinhibition process). Moreover, only the long-term cultivation either in continuous or batch operation mode, where the quasi-steady state is reached, is of biotechnological importance.…”
Section: Microalgae Growth In a Couette-taylor Bioreactor: Simulationmentioning
confidence: 52%
“…All the values needed to perform further calculations are summarized in Table 1 (u 1 is chosen accordingly to fulfill the condition u av = 1): Similarly as in our work [16], Lagrangian time-dependent simulation (data not shown) revealed that the state vector converges to a steady state in a few minutes (this is the time-scale of the photoinhibition process). Moreover, only the long-term cultivation either in continuous or batch operation mode, where the quasi-steady state is reached, is of biotechnological importance.…”
Section: Microalgae Growth In a Couette-taylor Bioreactor: Simulationmentioning
confidence: 52%
“…Models differed for numerical approaches and theories. They include: Eulerian-based partial differential equations, 13,[38][39][40] light dynamic imposition, [41][42][43] direct numeric simulation, 44 flow field imposition, 44 stochastic Lagrangian, [45][46][47][48] and energetic analysis. 49 Luo et al [50][51][52][53] proposed a model integrating kinetics, light distribution, and microalgal particle trajectories observed in an externally irradiated airlift photobioreactor by means of computer automated radioactive particle tracking (CARPT).…”
Section: Introductionmentioning
confidence: 99%
“…Simulated photobioreactors are useful for shedding light on the cultivation process of phytoplankton [10,32]. Algae in particular, such as H. pluvialis are cultivated en masse for valuable by-products; for example, carotenoids like Astaxanthin [35].…”
Section: Introductionmentioning
confidence: 99%
“…To date, most simulation work towards simulating photobioreactors has involved 1-dimensional models [10,32], to observe the effects of illumination variance. This emphasises exactly how important light availability is to cultivation efforts.…”
Section: Introductionmentioning
confidence: 99%